Central sensitisation in chronic pain conditions: latest discoveries and their potential for precision medicine. (May 2021) - Nijs, Jo; George, Steven Z; Clauw, Daniel J; Fernández-de-las-Peñas, César; Kosek, Eva; Ickmans, Kelly; Fernández-Carnero, Josué; Polli, Andrea; Kapreli, Eleni; Huysmans, Eva; Cuesta-Vargas, Antonio I; Mani, Ramakrishnan; et al.
Summary: Chronic pain is a leading cause of disability globally and associated with enormous health-care costs. The discrepancy between the extent of tissue damage and the magnitude of pain, disability, and associated symptoms represents a diagnostic challenge for rheumatology specialists. Central sensitisation, defined as an amplification of neural signalling within the CNS that elicits pain hypersensitivity, has been investigated as a reason for this discrepancy. Features of central sensitisation have been documented in various pain conditions common in rheumatology practice, including fibromyalgia, osteoarthritis, rheumatoid arthritis, Ehlers-Danlos syndrome, upper extremity tendinopathies, headache, and spinal pain. Within individual pain conditions, there is substantial variation among patients in terms of presence and magnitude of central sensitisation, stressing the importance of individual assessment. Central sensitisation predicts poor treatment outcomes in multiple patient populations. The available evidence supports various pharmacological and non-pharmacological strategies to reduce central sensitisation and to improve patient outcomes in several conditions commonly seen in rheumatology practice. These data open up new treatment perspectives, with the possibility for precision pain medicine treatment according to pain phenotyping as a logical next step. With this view, studies suggest the possibility of matching non-pharmacological approaches, or medications, or both to the central sensitisation pain phenotypes.